(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Most of the studies on fiber reinforced concrete contain use of only single type of fiber with different percentage and combination of materials. The use of two or more type of fibers in their suitable combinations may potentially not only improve the quality of concrete but may also improve performance. This process of mixing more than one fiber is called hybridization and mixture of fiber is known as hybrid fiber. Now days, paving block has remarkable demand because of their wide application in parking area, footpath, and petrol stations and also for their aesthetics etc. Paving block should have sufficient strength to bear heavy compressive load and offer good resistance to impact load. In this study, the comparison of polypropylene, steel and combination of both the hybrid fiber with percentage varying from 0 to 1 percent in paving block. The comparison is based on compression test, flexural test.